2019
DOI: 10.1021/acsnano.9b04050
|View full text |Cite
|
Sign up to set email alerts
|

Photoablation of Human Vitreous Opacities by Light-Induced Vapor Nanobubbles

Abstract: Myopia, diabetes and aging are the main causes of progressive vitreous collagen aggregation, resulting in vitreous opacities which can significantly disturb vision. As vitreous opacities, which induce the visual phenomenon of 'floaters', are accessible with nanomaterials and light, we propose a nanotechnology-based approach to locally ablate them with highly reduced light energy compared to the more traditional YAG laser therapy. Our strategy relies on the plasmon properties of gold nanoparticles that generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…As the eye is easily accessible to both light and advanced materials, our group has an interest in photothermal treatment of ophthalmological diseases. Recently we explored to which extent VNB may be suitable to destroy vitreous opacities (also named 'floaters') [105] ( Figure 8B). Eye floaters are protein aggregates mostly composed of a mixture of different types of collagen that are present in the vitreous [106,107].…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…As the eye is easily accessible to both light and advanced materials, our group has an interest in photothermal treatment of ophthalmological diseases. Recently we explored to which extent VNB may be suitable to destroy vitreous opacities (also named 'floaters') [105] ( Figure 8B). Eye floaters are protein aggregates mostly composed of a mixture of different types of collagen that are present in the vitreous [106,107].…”
Section: Lightmentioning
confidence: 99%
“…However, in vivo toxicity studies still need to be performed. vitrectomy of a patient treated with 10 nm HA-AuNPs respectively before and after illumination with a nanosecond laser ( 3 pulses of 800 µJ (adapted from [105]).…”
Section: Lightmentioning
confidence: 99%
“…If symptoms are clinically important and visual acuity levels drop, treatment can be considered. Vitrectomy is the gold-standard surgical treatment for patients with vision-degrading myodesopsia[ 30 ]. Of course, that option is used in a very limited number of cases considering the risks associated with this invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, that option is used in a very limited number of cases considering the risks associated with this invasive surgery. The other options that are currently being studied involve treatment with Nd:YAG laser vitreolysis[ 31 ] and photoablation[ 30 ]. However, those treatments are still experimental and not often used in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various types of nanoparticles (NPs) are found to assist laser treatments specially for treatment of eye diseases [17,18]. Sauvage et al reported on applying laser to ablate the plasmonic NPs conjugated with the vitreous opacities as feasible treatments for eye diseases [19]. In other research, laser has been used to trigger graphene nanosheets to release the drugs inside the eyes after administrations [20][21][22].…”
Section: Introductionmentioning
confidence: 99%